(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis examines the pedagogical technologies used to develop humanistic values among students through social media. In the digital era, social networks, blogs, video platforms and online communities influence students’ moral consciousness, communication culture and social behavior. Social media may strengthen empathy, tolerance, civic responsibility and respect for human dignity when it is used purposefully in education. At the same time, uncontrolled digital content may spread aggression, stereotypes, misinformation and moral indifference. Therefore, the development of humanistic values through social media requires a clear pedagogical strategy. The thesis analyzes value-oriented content selection, critical media analysis, reflective discussion, digital storytelling, project-based learning and ethical online communication as key technologies. The results show that social media can become an effective educational environment when it is integrated with humanistic pedagogy, media literacy and reflective learning.